Production Function Analysis of The New Kufa Cement Plant For The Period (2004-2020) - Abd AL Hussein Jalil AlGhaliby, Raad Ebraheem Neamah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The cement industry is an essential manufacturing industry that effectively enhances national income and achieves sustainable economic development. Its front and backlinks with various industrial sectors, and the importance of this industry is increasing in all countries alike. Extensive facilities to cover their need for this product and export the surplus. This industry is significant in Iraq due to the government's wars, which destroyed many infrastructures and disrupted the wheel of development. So, it became necessary to promote this industry again to push the wheel of reconstruction and infrastructure development forward. Given the importance of the new Kufa Cement Factory and its role in providing the local product as well as its contribution to promoting economic growth and employment of many human resources, as well as its contribution to strengthening and increasing the national development in terms of providing the product locally in the required quantities and quality, As well as concerning maintaining the balance of payments and providing foreign currency by closing the door to imported products that have always occupied the largest share of the Iraqi market in this aspect, it has been highlighted in this research.